Common Immunity. Roberto Esposito in Dialogue with Jacques Derrida and Peter Sloterdijk - Spina , Salvatore (E|C, 2024)
In this paper I will analyze the relationship between immunity and community in the contemporary philosophy. The aim of my work is to show how immunity and community are two faces of a same coin; they express the way through which it is possible to understand the form of the common living in the society. The first part of my paper analyzes the works of the Italian philosopher Roberto Esposito and examines in depth the concepts of communitas and immunitas; they are the names through which Esposito elaborates his biopolitics, beyond Michel Foucault’s thought. The second part proposes a confrontation between Esposito’s philosophy and the works of Jacques Derrida and Peter Sloterdijk. The most important concept, that emerges from their thoughts despite many differences, is co-immunity.